Tikrit University students exposed to ironic shows - Sabah Mohammed Tuama (Genius Journals, 2022)
The study aimed to monitor and follow up the exposure of students of Tikrit University to satirical programs, and used the descriptive method and the survey method, through the questionnaire that included a deliberate intentional sample of students of the Department of media the final stages of the Faculty of Arts, Tikrit University, as the sample was selected according to the intentional type because media students are the most the majority of the study sample members who are exposed to watching satirical programs by 45 and by a percentage of 90% of the total As for those who do not watch programs by 5 and by a percentage of 10%, the largest percentage of those watching satirical programs came via TV by 36 and by 46.15%, followed by watching programs via Facebook by 14 and by a percentage of 17.94% of the total sample.
Keywords: exposure, students, Tikrit University, satirical programs